Sexual Dimorphism in Morphometry of Length of Dry Adult Human Left Calcaneus (Bangladesh Journal of Anatomy, 2019)
Context: The determination of sex from an adult human skeleton is a fundamental task for forensic and physical anthropologists. The calcaneus, the largest tarsal bone, is a compact bone that can withstand high tensile forces. Length of calcaneus provide an additional reliable method for sex estimation via discriminant function analysis. Morphometric data of calcaneus is essential for plastic and reconstructive surgeons for proper management of various diseases of the foot. The present study intends to assess the dimorphic reliability of different length measurements of calcaneus.objective of the study is to assess different morphometry of length of dry adult human left calcaneus and to evaluate the morphological differences between male and female. Materials and Methods: The present study was a cross sectional analytical type of study conducted in the department of Anatomy, Dhaka Medical College, Dhaka from January 2018 to December 2018. The study material consists of two hundred left calcaneus of unknown sex. The study samples were distributed in male and female sex groups by ‘discriminant function analysis technique’. Maximum length, total length and length of the body of calcaneus were measured. Results: The mean ± SD of maximum length, total length and length of the body were significantly higher (p